Collapsibility of PMMA Based Material in Direct Investment Casting - Shukri, M.S.; Marwah, O.M.F.; Ibrahim, M.; Sharif, S.; Mohamad, E.J.; Hashim, M.Y. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Over recent years, the rapid growth of Additive manufacturing (AM) has benefits the Direct Investment Casting (DIC) process for intricate design in which significantly reduces the cost when associated with low volume production. Nevertheless, ceramic shells cracking has been recognized as critical problem when involved direct casting in which leads to incomplete collapsibility. Therefore, this study presents a numerical and experimental on poly(methyl) methacrylate (PMMA) pattern collapsibility for investment casting process and the stress analysis study on the ceramic shells. Study revealed that there were significant average of 5.8 % reduction of stress between square and polygon patterns. This study was conducted to examine the collapsibility of AM materials in the IC process.